A new species of the genus Dendrelaphis (Squamata: Colubridae) from Yunnan Province, China, with discussion of the occurrence of D. cyanochloris (Wall, 1921) in China - Jiang, Ke; Ren, Jin-Long; Guo, Jun-Feng; Wang, Zeng; Ding, Li; Li, Jia-Tang (Zootaxa, 2020)
A new species of the genus Dendrelaphis is described from Xishuangbanna, southern Yunnan, China, based on molecular and morphological data. The new species can be differentiated from other congeners by the following combination of characters: 1) ground color of body bronze, a black postocular stripe extending onto the neck only; 2) pale and dark ventrolateral stripe absent; 3) relatively indistinct transverse bands on the anterior part of lateral body; 4) loreal single; 5) vertebral scales strongly enlarged; 6) dorsal scale rows 15-15-11, all smooth; 7) ventrals 193–197, subcaudals 130–135, paired; 8) SVL/TOL ratio 0.292–0.301; 9) supralabials 9, 4th through 6th touching the eye; 10) the outermost row of dorsal scales the same color as other dorsal scales; 11) retracted hemipenis extending to the 6–7th subcaudal scales. According to molecular and morphological data, D. ngansonensis likely belongs to the D. cyanochloris complex. We further discussed D. cyanochloris complex from Tibet, Yunnan and Hainan, China. A key to Chinese species of Dendrelaphis is provided.